Phytochemical Screening and Antimicrobial activity of Terminalia catappa seed oil obtained from Anyigba, Kogi State, Nigeria, on Some Selected Clinical Isolates (The All Results Journal, 2020)
This research was carried out in a bid to seek for alternative ways of dealing with strains of microorganisms that have become resistant to conventional antibiotics. The study was carried out to evaluate the antimicrobial efficacy of Terminalia catappa seed oil obtained from Anyigba, Kogi State Nigeria, on some selected clinical isolates of selected microorganisms (Aspergillus niger, Staphylocuccos aureus, Escherichia coli). The oil was extracted from the seeds using the soxhlet extraction method with n-hexane as the solvent. The Mueller Hinton (well diffusion method) was used to test the susceptibility of the strains of the microorganisms to the oil, using Ciproflaxin as standard positive controls, alongside Tween and DMSO as negative control. Experiments were carried out in duplicates. The results obtained revealed that Terminalia catappa oil was unable to create any inhibition zones on the clinical isolates. From this research, it can be concluded that Terminalia catappa oil had no Antibacterial activity.